(untitled) (Research, Society and Development, 2020)
The objective was to study the effect of using fresh melon as an exclusive diet for beef cattle, observing the effects of this diet on biochemical parameters and liver histology. For the analysis of serum parameters, plasma concentrations of glucose, alkaline phosphatase, AST (aspartate aminotransferase), ALT (alanine aminotransferase) and urea were determined using the biochemical analysis systems ADVIA 1800® and Hitachi 917®. Microscopic analyzes (glycogen concentration and hepatic histopathology) were performed under an optical microscope, with a 40x magnification (Olympus CX31, Olympus Ótica Co, Japan). Blood metabolite values were within the normal range for the species with the exception of the glucose rate, which showed values ranging from 130.33 to 171.50 mg / dL, above normal values. Liver histology showed mild damage and accumulation of glycogen, conditions resulting from a diet rich in soluble carbohydrates. The exclusive melon diet is an alternative to replace part of the diet of beef cattle, it is important to observe the adaptation of the animals to the diet and the time to which they will be subjected to it.